The Role of Islamic Education Teachers in Instilling the Value of Religious Moderatio Amid the Polemic of Islamophobia - Wirani Atqia; Muhammad Syaiful Riky Abdullah (UIN Mataram, 2021)
This study aims to find and confirm the role of Islamic Religious Education teachers in instilling the value of religious moderation as an effort to prevent radicalism. With this form of radicalism having a bad effect on citizens and society, this fear has resulted in the emergence of a new perception, namely